Pengaruh Peningkatan Indeks Pembangunan Manusia (IPM) Terhadap Tingkat Pengangguran di Kabupaten Pasaman Barat - , Yulandari (STAIN Bengkalis, 2023)
This study looks at how raising the Human Development Index (HDI) affected West Pasaman Regency's unemployment rate between 2019 and 2022. The HDI, which combines indices of income, health, and education, is frequently used to gauge the standard of living in a community. The unemployment rate can also be a reflection of social welfare and economic situations. This study uses linear regression analysis to examine the association between these two variables. According to the study's findings, the HDI is still showing a steady upward trend even if the unemployment rate rose from 4.74% in 2019 to 6.01% in 2022. between 2019 and 2022, from 68.21 to 69.57. According to linear regression research, the HDI rises by 0.926 points for every 1% increase in the unemployment rate. The t test results demonstrate that there is a statistically significant relationship between unemployment and HDI. Even though a strong correlation was shown, this study also suggests that other factors are involved, such as advancements in the fields of socioeconomic policy, health, and education, which also affect changes in HDI. These results give policymakers valuable information for creating development initiatives that can lower unemployment rates and raise residents' standards of living in West Pasaman.